Dual-phase spinel Li4Ti5O12/anatase TiO2 nanosheet anchored 3D reduced graphene oxide aerogel scaffolds as self-supporting electrodes for high-performance Na- and Li-ion batteries. Issue 83 (15th November 2017) - Tian, Ye; Xu, Guobao; Wu, Zelin; Zhong, Jianxin; Yang, Liwen
Abstract : Self-supporting LTO-AT/RGO composite as anode materiel was prepared via a facile hetero-assembly, freeze-drying, mechanical compression and annealing. They exhibit excellent electrochemical capability when used for LIBs and SIBs. Abstract : Self-supporting electrodes consisting of dual-phase spinel Li4 Ti5 O12 /anatase TiO2 nanosheets and 3D reduced graphene oxide (RGO) aerogel for lithium ion batteries (LIBs) and sodium ion batteries (SIBs) were prepared via facile hetero-assembly, freeze-drying, mechanical compression and annealing. The 3D RGO aerogel acts as both conductive medium and self-supporting scaffold for anchored dual-phase nanosheets. The synergistic effect between the dual-phase nanosheets and the 3D highly conductive interconnected RGO network not only guarantees rapid reaction kinetics and strong structural stability of the electrodes during ion insertion/extraction, but also provides abundant accommodation for additional interfacial Li/Na storage. The self-supporting electrodes have desirable electrochemical performance such as a high reversible capacity (∼200/180 mA h g −1 for LIB/SIB at 1C/0.1C), good rate capability (∼141/117 mA h g −1 for LIB/SIB at 30C/10C) and superior cyclic performance (∼154/101 mA h g −1 for LIB/SIB at 10C/6C after 1000/700 cycles). Our results have great potential in constructing self-supporting RGO electrodes embedded with anode materials for LIB and SIB applications.